HER2 immunohistochemical scores provide prognostic information for patients with HER2‐type invasive breast cancer. Issue 4 (29th January 2019) - Tsai, Yi‐Fang; Tseng, Ling‐Ming; Lien, Pei‐Ju; Hsu, Chih‐Yi; Lin, Yen‐Shu; King, Kuang‐Liang; Wang, Yu‐Ling; Chao, Ta‐Chung; Liu, Chun‐Yu; Chiu, Jen‐Hwey; Yang, Muh‐Hwa
Abstract : Aims: Invasive breast cancer patients with human epidermal growth factor receptor 2 (HER2) immunohistochemical (IHC) scores of 3+ or 2+ with reflex in‐situ hybridisation (ISH) positivity are suitable for anti‐HER2 therapies. The aim of this study is to investigate whether the prognoses between IHC 3+ patients and IHC 2+/ISH+ patients are different. Methods and results: We analysed the clinicopathological information of 886 consecutive cases of HER2‐positive early breast cancer. The influences of the patients' age, cancer stage, hormone receptor status and anti‐HER2 treatment were adjusted using a multivariate Cox regression model. Both HER2 copy numbers and HER2 ISH ratios of the IHC 3+ group were significantly higher than those of the IHC 2+/ISH+ group. The outcomes of IHC 3+ patients were significantly better than those of IHC 2+/ISH+ patients in the univariate and multivariate analyses. HER2 copy numbers of ≥8 represented the best prognostic value, and it was chosen to be the cut‐off value. The reflex ISH for IHC 2+ patients with high HER2 copy numbers (≥8) predicted a better overall survival than that for those with low HER2 copy numbers. Conclusion: HER2 IHC scores and HER2 copy numbers can provide prognostic information for patients with HER2‐positive invasive breast cancer. Both IHC 3+ and IHC 2+ patients with high HER2 copy numbers had a better prognosis.